Head Injury in Infants and Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Of 738 children with head injuries (0-16 yrs) admitted to the Children's Memorial Hospital, Chicago, IL, during a 5-year period from 1981-85, 318 (43%) were less than 3 years of age and almost half of the younger group were under 1 year.